2020
DOI: 10.1039/c9tb01462d
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic and osteogenic effects of crocin and bicarbonate from calcium phosphates for potential chemopreventative and anti-inflammatory applications in vitro and in vivo

Abstract: Delayed healing and nonhealing of bone defects or resected bone sites remains an important clinical concern in the biomedical field.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 61 publications
1
18
0
Order By: Relevance
“…The hydrogels pHEMA@AgNPs(ELE)_2 and pHEMA@AgNPs(WBE)_2 were tested for in vitro toxicity against HCEC cells upon their incubation for a period of 24 h. The incubation of HCEC cells in the presence of pHEMA@AgNPs(ELE)_2 and pHEMA@AgNPs(WBE)_2 discs decreased their viability by 64.4 ± 5.7 and 72.8 ± 8.5%, respectively, compared with the cells that were incubated with pure pHEMA. According to ISO 10993-5, if the percent of cell viability is higher than ≥70%, then the material should be considered as non-cytotoxic [ 28 , 29 ]; therefore, the materials tested in this work are considered as low or nontoxic.…”
Section: Resultsmentioning
confidence: 99%
“…The hydrogels pHEMA@AgNPs(ELE)_2 and pHEMA@AgNPs(WBE)_2 were tested for in vitro toxicity against HCEC cells upon their incubation for a period of 24 h. The incubation of HCEC cells in the presence of pHEMA@AgNPs(ELE)_2 and pHEMA@AgNPs(WBE)_2 discs decreased their viability by 64.4 ± 5.7 and 72.8 ± 8.5%, respectively, compared with the cells that were incubated with pure pHEMA. According to ISO 10993-5, if the percent of cell viability is higher than ≥70%, then the material should be considered as non-cytotoxic [ 28 , 29 ]; therefore, the materials tested in this work are considered as low or nontoxic.…”
Section: Resultsmentioning
confidence: 99%
“…The %MIA(C) of 1 – 4 lies between −18.2 and −28.3%, whereas for the micelles SLS@ 1 – 4 , it is in a similar range (between −16.2 and −25.5%). According to ISO 10993-5 that regulates the “Biological evaluation of medical devicesPart 5: Tests for in vitro cytotoxicity”, if the percent of viability is higher than 70% upon treatment with an agent, this agent is considered as noncytotoxic . Therefore, conjugates 1 – 4 and their micelles are considered as nontoxic.…”
Section: Resultsmentioning
confidence: 99%
“…33 The Environmental Protection Agency (EPA) and the World Health Organization acknowledge that the data from this bioassay are effective and reliable in the determination of genotoxicity. 54 Moreover, the Allium cepa assay correlates to the results obtained from mammal test systems because of the similarity in chromosomal morphology. 33 Genotoxic effects of agents can be investigated by using bioindicator parameters such as the mitotic index (MI), chromosomal aberration (CA), nuclear abnormalities (NA), and micronucleus (MN) frequencies.…”
Section: In Vivo Genotoxicitymentioning
confidence: 99%
“…In contrast, the in vivo application of crocin showed pro-apoptotic and antiinflammatory effects in a rat model of femoral inflammation. These results suggest that crocin may have a therapeutic effect on osteosarcoma regulation and potential for use in wound healing during bone tissue regeneration (Koski et al, 2020). Studies have shown that in some diseases involving bone degeneration and dysregulation of bone homeostasis besides osteogenesis, the influence of osteoclast formation and osteoimmunomodulation is important (Chen et al, 2017b; Chen…”
Section: Effects Of Crocin On Cell Differentiationmentioning
confidence: 98%
“…The final product of these cascades is the expression of tartrate-resistant acid phosphatase (TRAP) and other enzymes, which are involved in osteoclast-mediated bone resorption (Asagiri and Takayanagi, 2007) Crocin can be considered a safe substance to promote osteogenic differentiation of BMSCs (B. Li et al, 2020) hBMSCs/10-50 µM (10-500 mg/ml) Increased LAP activity, calcium nodules, and RUNX2, COL1A1, and OCN expression, decreased GSK-3β phosphorylation Crocin is effective in in-vitro and in-vivo osteogenic models Zhu et al (2019) M2 macrophages and BMSCs/40 and 80 µM (400-800 mg/ml) Promoted M2 phenotype that was decreased in antiinflammatory cytokine-induced osteogenic differentiation of BMSCs in co-culture with pre-treated macrophages through inhibition of p38 and c-Jun N-terminal kinase signaling Crocin has therapeutic potential for bone degenerative diseases through induction of M2 macrophage polarization, resulting in inflammation reduction and osteogenic differentiation of BMSCs Koski et al (2020) hFOBs and MG-63 cell line, Rats/ 45 µg (450 mg/ml) Increased osteoblast proliferation and decreased osteosarcoma viability and pro-apoptotic and antiinflammatory effects in-vivo Crocin has a potential therapeutic effect on osteosarcoma regulation and uses for wound healing during bone tissue regeneration Crocin decreases osteoclast function and differentiation and bone resorption in-vitro, as well reduction in bone resorption activity of osteoclasts osteoclast-specific gene expression, including NFATc1, c-Fos, and cathepsin, are involved, leading to inhibition of bone resorption activity (Fu et al, 2017). A similar study by Shi et al demonstrated that crocin downregulates osteoclast differentiation via inhibition of JNK and NF-κB signaling pathways in BMM cells in vitro.…”
Section: Effects Of Crocin On Cell Differentiationmentioning
confidence: 99%